GAMBARAN PERSEPSI MAHASISWA TENTANG LINGKUNGAN BELAJAR AKADEMIK DI JURUSAN KEPERAWATAN POLTEKKES KEMENKES PALANGKA RAYA TAHUN 2025 - Baharuddin Yusuf; Arizal; Sucipto Dwitanta (Berajah Journal, 2025)
Academic achievement is influenced by an academic learning environment that is optimal for learning and development. One way to assess the academic learning environment for students is to measure student perceptions. The purpose of this study was to determine students' perceptions of the academic learning environment. This study is a qualitative survey using the DREEM questionnaire. The results of the study obtained a score of 152.06 points (76.03%) out of a maximum of 200 points. The conclusion of this study is that students majoring in Nursing at the Palangka Raya Ministry of Health Polytechnic have a very good perception of the academic learning environment in 2025.